THE HETEROGENEOUS UPPER MANTLE LOW VELOCITY ZONE - Thybo H. (My University, 2006)
The upper mantle low velocity zone (LVZ) is a depth interval with slightly reduced seismic velocity compared to the surrounding depth intervals. The zone is present below a relatively constant depth of 100 km in most continental parts of the world, both in cratonic areas with high average velocity and tectonically active areas with low average velocity. Evidence for the low velocity zone arises from controlled and natural source seismology, including studies of surface waves and of primary and multiple reflections of body waves from the bounding interfaces, calculations of receiver functions, and absolute velocity tomography. The available data indicates a more pronounced reduction in seismic velocity and Q-value for S-waves than P-waves as well as high electrical conductivity in the LVZ. Seismic waves are strongly scattered by the zone, which demonstrates the existence of small-scale heterogeneity. The depth to the base of the LVZ is systematically shallower in cold, stable cratonic areas than in hot, active regions of the world. Because of its global occurrence below a relative constant depth of 100 km, the LVZ cannot be explained by metamorphic or compositional variation and rheological changes. Calculated upper mantle temperatures indicate that the rocks are close to the solidus in an interval with variable thickness below 100 km depth, provided that the rocks contain water and carbon dioxide. The presence of, even small amounts of such fluids in the mantle rocks will lower the solidus by several hundred degrees and introduce a characteristic kink on the solidus curve around 80-100 km depth. The seismic velocities and Q-values are significantly reduced of rocks, which are close to the solidus or contain small amounts of partial melt. Hence, the LVZ may be explained by upper mantle temperatures being close to the solidus in a depth interval below 100 km. Assuming that the rocks contain only limited amounts of fluids, this mechanism may explain the low velocities, Q-values, and resistivity, as well as the intrinsic scattering, and the characteristic variation in thickness of the low velocity zone. © 2005 Elsevier B.V. All rights reserved.
Keywords: 8° DISCONTINUITY; ATTENUATION; LEHMANN DISCONTINUITY; LOW VELOCITY ZONE; MANTLE; SCATTERING; SEISMIC VELOCITY